Space-time channel modeling for emerging wireless techniques : a system-dependent approach - Chen, Yi Fan (2008)
In the past decade, the wireless industry continues to revolutionize and develop new technologies. Emerging wireless systems like ultrawideband (UWB) radio and smart antennas have defied channel characterization by the paradigm of traditional approaches. This is due to the fact that the technologies either occupy a large fractional bandwidth or utilize a large array to form narrow beams, which will significantly influence the definition of the channel. The need is now greater than ever for more accurate space-time channel models with emphasis laid on the question how to integrate the system dependency into the parametric model.